Functional characterization of the BnNCED3 gene in Brassica napus. (March 2017) - Xu, Peipei; Cai, Weiming
Highlights: The Brassica napus NCED family protein BnNCED3 shared high amino acid sequence identity with the AtNCED3 protein. The overexpression of BnNCED3 contributes to ABA accumulation, NO and ROS generation in transgenic Arabidopsis plants, thereby enhancing abiotic stress tolerance. Expression pattern assays revealed that BnNCED3 is highly expressed in senescencing leaves. BnNCED3 involvement in the control of the inhibition of seed germination, lateral root initiation, and early phase changes, and ABA bio-synthesis is required for the BnNCED3-mediated leaf senescence phenotype. Abstract: Abscisic acid (ABA) has been implicated in plant adaptation to various environmental stresses and the regulation of seed dormancy, leaf senescence and organ abscission progression. The cleavage of cis -epoxycarotenoids by 9- cis -epoxycarotenoid dioxygenase (NCED) family proteins is a critical step in the regulation of abscisic acid (ABA) synthesis in plants. In the present study, the NCED family gene BnNCED3 was isolated from Brassica napus . BnNCED3 encodes a 592-amino acid protein with high amino acid sequence similarity to the Arabidopsis AtNCED3 protein. Expression pattern assays revealed that BnNCED3 is ubiquitously expressed at different levels in all the examined organs. Furthermore, the overexpression of BnNCED3 contributed to ABA accumulation and NO and ROS generation in transgenic Arabidopsis plants, thereby enhancing abiotic stress tolerance. These experiments also indicated the involvement of BnNCED3 in the control of plant development in transgenic Arabidopsis, such as the inhibition of seed germination, lateral root initiation, early phase changes and the enhancement of ABA-associated leaf senescence. Together, these results indicated that BnNCED3 is at least partly involved in both stress adaptation and plant development through the regulation of ABA biosynthesis.